Structure of Macroeconometric Model of the Knowledge-Based Economy W8D-2010 and Its Extensive Databases - Florczak, Waldemar; Gosińska, Emilia; Leszkiewicz-Kędzior, Katarzyna; Welfe, Władysław (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The endogenous theory of growth provides the theoretical underpinning for modelling the knowledge-based economies, which justifies its use to establish the structure and major properties of the new macroeconometric W8D-2010 model of the Polish economy. The paper presents the structure of a new version of the W8D model and describes databases of W-models, covering many hundreds of time series original and transformed. In addition, the methods of time-series analysis are discussed, including tests for the order of integration and structural parameter estimation techniques. Because non-stationary variables are present in the system, the Engle-Granger two-step procedure was indicated as preferred due to the use of ECM allowing for decomposition of adjustment mechanism into long-run and short-run effects.